Development of Digital Worksheet Based on Ngerti, Ngrasa, Nglakoni to Improve College Student Lifeskill - Wijayanti, Astuti; Ernawati, Tias (Unnes Science Education Journal, 2020)
The application of technology in education in the 4.0 era can make it easier for students to build their knowledge. The model of this research is the Research and Development of Borg and Gall which was modified by Sukmadinata (2006) conducted to describe the development of a Tringo-based digital worksheet that is suitable for use in lectures on Natural Sciences III to increase students' lifeskill. This article discusses the Develop phase. Data collection techniques using a questionnaire technique. From the results of the study it can be concluded that the Digital Worksheet is appropriate to be used in Science III lectures with the average results of expert validator ratings on each aspect as follows: content worthiness of 32.25 (Very Good), Conformity of presentation with learning approaches of 36 (Very Good), Conformity with didactic requirements is 18.5 (Very Good), Conformity with construction requirements (linguistic) is 20 (Good) and Conformity with technical requirements (graphic) is 26.75 (Very Good). The validation results of tringo-based Digital worksheets are declared to meet valid criteria by the validator with an average total validity of 4.0 (valid). The use of digital worksheets was responded positively by students at 80.4% and Lecturers of Natural Sciences III at 84.4%.